Dampak Dari Faktor Spesifik Perusahaan Terhadap Profitabilitas Perusahaan(Studi Pada Perusahaan Manufaktur Yang Terdaftar DiBursa Efek Indonesia) - Puspita, Ranika Romadhona; , Drs. Ma'ruf,MM (2017)
This study aims to determine the impact of specific factors of companies consisting of firm size, leverage, firm growth on the profitability of companies in the manufacturing companies listed in Indonesia Stock Exchange 2011-2015. The population in this study using Manufacturing Company listed on the Indonesia Stock Exchange 2011-2015. The research sample as many as 31, the company, which was recorded in ICMD, where the sample method used was purposive sampling is a sampling method that takes an object with certain criteria. Data analysis method used is multiple linear regression analysis and hypothesis testing using t-test statistic, the F-statistic and the coefficient of determination. From the analysis during the observation period t test results showed that the variables of firm size and leverage significantly negative effect on profitability, while firm growth significantly positive effect on profitability. The results of the F test analysis found that the variable firm size, leverage, firm growth together significant effect on profitability. The results of the analysis of the coefficient of determination (R ²) were obtained R square (R ²) of 0,241, this shows that the profitability can be explained by Firm Size, Leverage, Firm Growth amounted to 24,1%, while the remaining 75,9% is explained influenced by factors other outside variables studied. Keywords: Firm Size, Leverage, Firm Growth, Profitability